2011
DOI: 10.4310/mrl.2011.v18.n1.a1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic linearity of regularity and $a^*$-invariant of powers of ideals

Abstract: Abstract. Let X = Proj R be a projective scheme over a field k, and let I ⊆ R be an ideal generated by forms of the same degree d. Let π : X → X be the blowing up of X along the subscheme defined by I, and let φ : X →X be the projection given by the divisor dE 0 − E, where E is the exceptional divisor of π and E 0 is the pullback of a general hyperplane in X. We investigate how the asymptotic linearity of the regularity and the a * -invariant of I q (for q ≫ 0) is related to invariants of fibers of φ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…the minimal number such that I is integral over I ≤d , where I ≤d denotes the ideal generated by the forms in I of degree at most d. The other coefficient, e, is more mysterious. In the case where I is m-primary and generated by general forms of a single degree, I determines a finite morphism φ : Proj(S) → P r , and [EH10] showed that e+ 1 is the maximum regularity of a fibre of φ; following a conjecture of [Hà10], [Char10] extended this result to the case in which I is generated by arbitrary forms of a single degree in terms of the associated map from the blowup of Proj(S) along the subscheme defined by I. This is quite a tantalizing phenomenon, but so far no similar interpretation has presented itself in a more general case.…”
Section: Introductionmentioning
confidence: 99%
“…the minimal number such that I is integral over I ≤d , where I ≤d denotes the ideal generated by the forms in I of degree at most d. The other coefficient, e, is more mysterious. In the case where I is m-primary and generated by general forms of a single degree, I determines a finite morphism φ : Proj(S) → P r , and [EH10] showed that e+ 1 is the maximum regularity of a fibre of φ; following a conjecture of [Hà10], [Char10] extended this result to the case in which I is generated by arbitrary forms of a single degree in terms of the associated map from the blowup of Proj(S) along the subscheme defined by I. This is quite a tantalizing phenomenon, but so far no similar interpretation has presented itself in a more general case.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies are devoted to investigating these constants (cf. [4,10,18,19,25]). Even for edge ideals of graphs the exact values for these constants are still out of reach.…”
Section: Open Problems and Questionsmentioning
confidence: 99%
“…To find the exact form of the linear function is also not easy (cf. [1,6,11,38]). In the following, we will call them the linearization-of-regularity problems, by abuse of terminology.…”
Section: Introductionmentioning
confidence: 99%